2007
DOI: 10.1161/01.str.0000257304.21967.ba
|View full text |Cite
|
Sign up to set email alerts
|

Site of Arterial Occlusion Identified by Transcranial Doppler Predicts the Response to Intravenous Thrombolysis for Stroke

Abstract: Background and Purpose-The objective of this study was to examine clinical outcomes and recanalization rates in a multicenter cohort of stroke patients receiving intravenous tissue plasminogen activator by site of occlusion localized with bedside transcranial Doppler. Angiographic studies with intraarterial thrombolysis suggest more proximal occlusions carry greater thrombus burden and benefit less from local therapy. Methods-Using validated transcranial Doppler criteria for specific arterial occlusion (Thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
484
3
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 635 publications
(514 citation statements)
references
References 45 publications
15
484
3
12
Order By: Relevance
“…The same group confirmed earlier observations that an occlusion of the distal internal carotid artery can hardly recanalized with I.V. TPA [14,15]. Another group showed that the effect of I.V.…”
supporting
confidence: 82%
“…The same group confirmed earlier observations that an occlusion of the distal internal carotid artery can hardly recanalized with I.V. TPA [14,15]. Another group showed that the effect of I.V.…”
supporting
confidence: 82%
“…Although intravenous (IV) thrombolysis with tissue plasminogen activator (tPA) has been approved by the Food and Drug Administration (FDA) since 1996, it has been used in only 3 to 4% of ischemic stroke patients due to major limitations and a narrow 3-to 4.5-h treatment window [1,2]. The benefit of IV tPA is limited, both in regard to clinical and recanalization efficacy, particularly for large vessel occlusions, the most common cause of severe and fatal AIS [3,4]. Large vessel occlusions are however amenable to endovascular therapy, not unlike acute coronary syndromes presenting as ST segment elevation myocardial infarction, which are better treated with percutaneous interventions rather than IV thrombolysis [5].…”
Section: Introductionmentioning
confidence: 99%
“…21 According to more recent studies, ultrasound-enhanced thrombolysis may augment tissue plasminogen activator induced arterial recanalization by continuous transcranial Doppler. 22 Symptomatic hemorrhagic transformation of the infarction remains the primary concern with the administration of intravenous rtTPA. 23,24 Despite the apparent risks of ICH, atrial fibrillation patients not on warfarin should always be promptly referred for thrombolysis whenever they are eligible.…”
Section: Initial Evaluationmentioning
confidence: 99%